Pelaksanaan Perjanjian Tertutup (Tying Agreement) Oleh PT Pelabuhan Indonesia II (PERSERO) Pada Area Konsesi Pelabuhan Dalam Perspektif Hukum Persaingan Usaha - Kahfiarsyad Julyan Elevenday (Riau Law Journal, 2020)
This study aims to find out about how the monopoly activities including how the implementation of a tying agreement conducted by PT Pelabuhan Indonesia II (Persero) as a SOE in the perspective of Competition Law. This study is conducted by analyzing the consideration of judges as stated in the Supreme Court of Republic Indonesia Decision No. 302 K/Pdt. Sus-KPPU/2014 and North Jakarta District Court Decision No. 1/Pdt/KPPU/2015/PN Jkt.Utr. The results of this study indicate that the monopoly activities conducted by PT Pelabuhan Indonesia II (Persero) in its concession area are a monopoly by law as stated in Article 50 a Law Number 5 Year 1999 concerning The Prohibition of Monopolistic Practices and Unfair Business Competition because the monopoly activity referes to Law Number 17 Year 2008 concerning Shipping which regulates that to conduct commercial activities at the port needs a concession agreement that given by the port operator. The implementation of a tying agreement made by PT Pelabuhan Indonesia II (Persero) is not against the Law Number 5 Year 1999 concerning The Prohibition of Monopolistic Practices and Unfair Business Competition because if a rule of reason approach is used in the case, then the positive impact resulting from the implementation of tying agreement is greater that the negative impact. Keywords: Tying Agreement, Monopoly, State Owned Enterprise, Port, Business Competition